The election of a world champion - Martin Langen; Thomas Krauskopf (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2010)
This paper examines the mechanisms by which a World Champion is chosen in the For-mula One Championship. Furthermore it is analysed whether there is a best method to do this. For this purpose we will discuss the methods used by the Fédération Internationale de l'Automobile (FIA) since the founding of the World Championship in 1950. We show how the election of a method affects the Formula One contest. We then give insight whether there is a best method to select a World Champion or not. We therefore discuss Arrow's Impossible Theorem with respect to this sports contest. Moreover we simulated several seasons and compared different scoring vectors with respect to indicators that might be important for viewer's demand.
Keywords: D71; L83; C63; 330; Social Choice; Aggregation rules; Ranking; Sport; Formula One